The Effect of Inhalation of Kaffir Lime (Citrus Hystrix) and Boiled Ginger Water on the Frequency of Nausea and Vomiting (Emesis Gravidarum) in Pregnant Women - Kurnaesih, Een; Rizqiani Rusydi, Arni; A. Fachrin, Suharni; Baharuddin, Alfina; Azzahra, Fatimah (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
Pregnant women who experience ongoing emesis of gravidarum can be dehydrated, which will interfere with their pregnancy. Through non-pharmacological measures, namely ginger drink or inhalation of kaffir lime, can reduce the frequency of nausea and vomiting in pregnant women. The design of this study used an experiment with two groups, Pretest-Posttest. The sample of this study was some pregnant women who were in the working area of the Macini Sawah Health Center Makassar city, as many as 30 people divided into two groups, with details of 15 people being given kaffir lime inhalation and 15 other people being given ginger decoction. The results showed that from 15 respondents before being given ginger water, 15 people experienced nausea and vomiting (100%), and after being given ginger water, two people experienced nausea and vomiting three times (13.3%), and two people had nausea and vomiting. 13 people (86.7%). The results showed that before giving kaffir lime therapy, the average frequency of nausea and vomiting was 4-5 times. The results of the statistical tests obtained p value = 0.017, and then there is an effect of giving boiled ginger water with the frequency of nausea and vomiting in pregnant women. Research shows that giving Inhaled Kaffir lime and ginger water decoction has an effect on nausea and vomiting in pregnant women. It is recommended that health workers be able to provide additional and motivate them to overcome nausea and vomiting by giving non-pharmacological drugs by inhalation.